Development of Rice Variety With Durable and Broad-Spectrum Resistance to Blast Disease Through Marker-Assisted Introduction of Pigm Gene - Feng, Zhiming; Li, Mingyou; Xu, Zhiwen; Gao, Peng; Wu, Yunyu; Wu, Keting; Zhao, Jianhua; Wang, Xiaoqiu; Wang, Jianan; Li, Mengchen; Hu, Keming; Chen, Hongqi; et al. (Frontiers in Plant Science, 2022)
Rice blast, caused by Magnaporthe oryzae (M. oryzae), is one of the most destructive diseases threatening rice production worldwide. Development of resistant cultivar using broad-spectrum resistance (R) gene with high breeding value is the most effective and economical approach to control this disease. In this study, the breeding potential of Pigm gene in geng/japonica rice breeding practice in Jiangsu province was comprehensively evaluated. Through backcross and marker-assisted selection (MAS), the Pigm was introduced into two geng rice cultivars (Wuyungeng 32/WYG32 and Huageng 8/HG8). In each genetic background, 5 advanced backcross lines with Pigm (ABLs) and same genotypes as the respective recurrent parent in the other 13 known R gene loci were developed. Compared with the corresponding recurrent parent, these ABLs all exhibited stronger resistance in seedling inoculation assay using 184 isolates collected from most rice growing regions of the lower region of the Yangtze River. With respect to panicle blast resistance, all ABLs reached high resistant level to blast disease in three consecutive years’ tests with the inoculation of total 7 mixed-conidial suspensions collected from different regions of Jiangsu province. In natural field nursery assays, the ABLs showed significantly higher resistance than the recurrent parents. No common change on importantly morphological traits and yield-associated components was found among the ABLs, demonstrating the introduction of Pigm had no tightly-linked undesirable effect on rice economically important traits and its associated grain weight reduction effect could be probably offset by others grain weight genes or at least in the background of the above two varieties. Notably, one rice line with Pigm, designated as Yangnonggeng3091, had been authorized as a new variety in Jiangsu province in 2021, showing excellent performance on both grain yield and quality as well as the blast resistance. Together, these results suggest that the Pigm gene has a high breeding value in developing rice varieties with durable and broad-spectrum resistance to blast disease.